You can't fire everyone : and other lessons from an accidental manager - Gilman, Hank. (New York : Portfolio/Penguin, 2011)
A reference for bosses who never aspired to enter management draws on the author's sometimes haphazard experiences of nurturing talent throughout his career, sharing recommendations for such areas as leading with respect and handling troublesome workers.
Friendless -- Recruiting and managing the "talent" -- The cardinal sins of hiring (and the dumb things you do right after) -- You're fired! -- Optics, or paying attention to how things look -- The well-behaved manager -- Managing in a crisis -- The modern manager -- There's no such thing as a small role -- Director's cut.
Includes index.
Keywords: Supervision of employees; Management; Interpersonal relations